ATANAS DALCHEV’S SILENCE AS A LITERARY-HISTORICAL TOPOS - Kamen Rikev (Езиков свят)
The paper argues that the period of limited poetic activity of the prominent Bulgarian author Atanas Dalchev in the years 1945–1965, should be regarded not only as a biographical, but rather a significant literary-historical topos. This period, most often described as “Dalchev’s silence” by literary historians and critics, is often discussed in relation to the author’s works, and inspires comparisons to other Bulgarian writers, such as Nikolay Liliev. The paper outlines the origin of the concept, its development and interpretations in the years 1966–1990, as well as its transformation into a metaphor for civil dignity. It refers to comments made by, among others, Panteley Zarev, Atanas Lazovski, Boris Delchev, Milena Tsaneva, Svetlozar Igov, Georgi Markov, Edvin Sugarev, Bozhidar Kunchev, Roman Hadzhikosev, Angel Igov, Noemi Stoichkova, Yordan Efftimov and Toni Nikolov. It is revealed that the notion of “silence” in regard to Dalchev’s post-war works can only be used conditionally. The analysis allows to conclude that while in the years of totalitarianism the breaking of Dalchev’s silence was willingly interpreted as a manifestation of a public (and politically correct) position, or even a kind of enlightenment of the poet about the radically changed political reality, after 1990, conversely, the concept became a sign of non-conformism expressed by creative and civil bravery.